International Exhibition - Jeonnam International SUMUK Biennale - Antoniou, Klitsa (My University, 2026)
2021 2021 Jeonnam International SUMUK Biennale Sunset Art Museum, and ChoHeeryong Art Museum Curated by Seung Mi Sinan, South Korea